Resistance exercise interventions to elderly people diagnosed with sarcopenia. A systematic review - Solano García, Wilson (2018)
Purpose: Examine the evidence generated by the resistance exercise based interventions to elderly people diagnosed with Sarcopenia. Methods: A literature review was carried out by combining keywords in the following databases: EBSCO HOST; OVID; PROQUEST: Public health data base, Research library; SCIENCE DIRECT; SPRINGER LINK; COCRANE LIBRARY; PUBMED; SCIELO; LILACS; PEDro. A total of 7819 studies were obtained in which five of them met the inclusion criteria: experimental articles, resistance exercise as intervention, full-text, English-Spanish language, adults over age 60 diagnosed with Sarcopenia. Results: Most of the studies revealed increases in percentages of change in the variables associated with the Sarcopenia, muscle mass (3.28%), muscle strength (19.16%) and muscle function (18.12%). After analyzing the details of the interventions, they showed improvements when working at least 12 weeks with a frequency of 2-3 days for 60 minutes session, stimulating the major muscle groups at intensities between 60-85% (1RM) for 3 series between 6- 15 repetitions with 1-2 minutes rest between series. Similar benefits are obtained when exercising through biomechanical machines or free weight exercises. Conclusions:     Resistance exercise improves the physical variables associated with sarcopenia in people with this syndrome. After analyzing the recommendations of exercise prescription to counteract the effects of Sarcopenia based on the people who did not have sarcopenia and compared to those found in the present study, it is shown that the results are similar.   Keywords: muscle mass, physical performance, muscle strength, older people, aging.